Development of Teaching Materials on Vesicular-Arbuscular Mycorrhiza (VAM) Topic for Biotechnology Course in Science Education Undergraduate Program - Paula Nita Tandaju; Jovialine Albertine Rungkat; Ester Caroline Wowor (Universitas Muhammadiyah Enrekang, 2024)
This research aims to develop teaching materials on the topic of vesicular-arbuscular mycorrhiza (VAM) for biotechnology courses in the science education undergraduate program at Universitas Negeri Manado that are suitable for use. This type of research is the research and development (R&D) model by Borg & Gall. The research steps consist of (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, and (6) product trial (small group trial). The research instrument we used was a questionnaire consisting of a material expert validation questionnaire, a media expert validation questionnaire, and a small group product trial questionnaire. The results of expert validation showed that the material expert was 93% and the media expert was 93%. The percentage obtained is included in the very good category, so it is feasible to use. Furthermore, the product trial in a small group consisting of 7 students in the Science Education Undergraduate Program obtained a result of 92%, including in the very good category. Thus, the teaching materials that have been successfully developed on the topic of vesicular-arbuscular mycorrhiza (VAM) for biotechnology courses in the Science Education Undergraduate Program at Universitas Negeri Manado are declared fit for use in lectures.